Development of Natural Cation Exchanger for the Treatment of Lead ions from Aqueous Solution - Homagai, Puspa Lal (Journal of Nepal Chemical Society, 2013)
Cellulose, hemicelluloses and lignin are the main constituents found in sugarcane (Saccharum officinarum) bagasse having many surface active sites containing hydroxyl and/or phenolic groups which are effective for chemical modification. The biowaste was first charred with concentrated sulphuric acid and then the charred aminated sugarcane bagasse (CASB) was prepared by reduction followed by oxidation. The developed bio-sorbent was characterized by SEM, TGA/DTA, FTIR and elemental analysis. Batch adsorption methods were carried out to determine Pb+2 sorption capacities at different pH ranges and sorbate concentrations. The maximum adsorption capacity for Pb+2 was found to be 323 mg g-1 with an efficiency of 98% at pH 4.The experimental data showed a good fit to Langmuir isotherm as compared to Freundlich isotherm models. The kinetics was best fitted with the pseudo-second order model. The adsorption equilibrium was attained within 20 min. The high adsorption capacity and fast kinetics results of the charred aminated sugarcane bagasse indicated that it might be potential adsorbent for the removal of lead from contaminated water. DOI: http://dx.doi.org/10.3126/jncs.v29i0.9235 Journal of Nepal Chemical Society Vol. 29, 2012 Page: 34-43 Uploaded date : 12/3/2013